2022
DOI: 10.1186/s43074-022-00065-1
|View full text |Cite
|
Sign up to set email alerts
|

From compressive sampling to compressive tasking: retrieving semantics in compressed domain with low bandwidth

Abstract: High-throughput imaging is highly desirable in intelligent analysis of computer vision tasks. In conventional design, throughput is limited by the separation between physical image capture and digital post processing. Computational imaging increases throughput by mixing analog and digital processing through the image capture pipeline. Yet, recent advances of computational imaging focus on the “compressive sampling”, this precludes the wide applications in practical tasks. This paper presents a systematic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…In addition to spectral SCI reconstruction as shown in this work, we do believe our network can be used in medical images [ 59 ], image compression [ 60 ], temporal compressive coherent diffraction imaging [ 61 ], and video compressive sensing [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to spectral SCI reconstruction as shown in this work, we do believe our network can be used in medical images [ 59 ], image compression [ 60 ], temporal compressive coherent diffraction imaging [ 61 ], and video compressive sensing [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary experiments found that inexact gradients could accelerate the backward passes in training our models by roughly 1.3 ∼ 1.5×. Another direction is to integrate DEQ with semantic analysis in SCI (Zhang et al 2022).…”
Section: Future Workmentioning
confidence: 93%
“…Cascaded metasurfaces (CM) have emerged as a typical platform to provide dynamic switchable abilities, by virtue of modulating complex diffraction modes and angular spectrum through pixellevel alignment with high precision. [22][23][24][25] Some interesting optical phenomenon can be generated, for example, multilayer optical neural networks, [26][27][28][29] encryption, and decryption of optical secret sharing [30] are urgently exploited by the combination of metasurfaces. Other applications by applying orbital angular momentum multiplexing and demultiplexing, [31] switchable holographic display [32,33] have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%